Self Stigma and Burden Among Caregivers of Persons with Schizophrenia in Community: Cross Sectional Study - Suharsono; Isworo, Adi; Faidah, Noor (PT. Anagata Sembagi Education, 2025)
Background: Caregivers of individuals with schizophrenia often experience significant psychological and emotional challenges, including self-stigma and caregiver burden. Understanding these phenomena is essential to develop supportive interventions. Objective: This study aimed to examine the levels of self-stigma and caregiver burden among caregivers of persons with schizophrenia living in the community and to explore the relationship between these two variables. Methods: A cross-sectional study design was employed involving 100 caregivers selected through purposive sampling. Data were collected using validated self-report questionnaires: the Self-Stigma of Family Members Scale (SSFS) and the Zarit Burden Interview (ZBI). Descriptive statistics and Pearson correlation analysis were conducted to assess the relationship between self-stigma and caregiver burden. Results: The findings indicated that a majority of caregivers experienced moderate to high levels of both self-stigma and caregiver burden. A significant positive correlation was found between self-stigma and caregiver burden (p < 0.01), indicating that higher levels of self-stigma were associated with greater caregiver burden. Conclusion: Self-stigma contributes to the burden experienced by caregivers of individuals with schizophrenia in the community. Interventions aimed at reducing stigma may help alleviate the psychological burden among caregivers and improve their well-being.